A novel approach based on the ultrasonic-assisted microwave method for the efficient synthesis of Sc-MOF@SiO2 core/shell nanostructures for H2S gas adsorption: A controllable systematic study for a green future - Muzammil, Khursheed; Solanki, Reena; Alkaim, Ayad F.; Romero Parra, Rosario Mireya; Lafta, Holya A.; Jalil, Abduladheem Turki; Gupta, Reena; Hammid, Ali Thaeer; Mustafa, Yasser Fakri (Frontiers in Chemistry, 2022)
In this work, for the first time, novel Sc-MOF@SiO2 core/ shell nanostructures have been synthesized under optimal conditions of ultrasonic assisted microwave routes. The final products showed small particle size distribution with homogeneous morphology (SEM results), high thermal stability (TG curve), high surface area (BET adsorption/desorption techniques) and significant porosity (BJH method). the final nanostructure of Sc-MOF@SiO2 core/ shell with such distinct properties was as a new compound for H2S adsorption. the was used with the systematic investigation based on 2K-1 factorial design showed high performance adsorption about 5 mmol/g for these novel adsorbents, the optimal experimental conditions included pressure: 1.5 bar, time contact: 20 min and temperature: 20 °C. This study and its results promise a green future for potential controlling the gas pollutant.